PENGEMBANGAN BAHAN AJAR PROGRAM LINEAR BERBASIS KONTEKSTUAL DAN ICT - Swaditya Rizki; Nego Linuhung (UNIVERSITAS MUHAMMADIYAH METRO, 2016)
This study is a research and development (R & D). The model used in this research is to adapt the development of the 4D model (Define, Design, Develop, Disseminate) developed by Thiagarajan. This study aims to generate the teaching materials based contextual and ICT are good at program linear and to determine the effectiveness of teaching materials based contextual and ICT at program linear on learning outcomes. Data collection instruments used in this study in the form of questionnaires, interviews, sheet validation, and matter. Data analysis techniques used in this research and development is a qualitative descriptive analysis technique to calculate the average, while for influence before and after treatment that uses the analysis of paired sample t-test. The conclusions obtained from the development are teaching materials based contextual and ICT are very valid and practical for use in the learning process. From the test results, it can be concluded that there is a very significant influence mathematics teaching materials based contextual and ICT on student learning outcomes. So, teaching materials based contextual and ICT is very effective for use in learning the material Program Linear